Sentinel Lymph Node Biopsy Versus Elective Neck Dissection: Long-Term Oncologic Outcomes in Clinically Node-Negative Tongue Cancer - Park, Woori; Jin, Hokyung; Heo, Yujin; Jeong, Han-Sin; Son, Young-Ik; Chung, Man Ki; Baek, Chung-Hwan (Clinical and experimental otorhinolaryngology, 2022)
Objectives. The aim of this study was to compare the long-term oncologic outcomes of sentinel lymph node biopsy (SLNB) versus elective neck dissection (END) in clinically node-negative (cN0) tongue cancer.Methods. This was a retrospective cohort study of patients with cN0 tongue cancer from a single institution, including 91 patients in the SLNB group and 120 patients in the END group.Results. The overall recurrence rate showed no significant difference between the two groups. The regional control rate was also comparable between the two groups (P=0.490). The 5-year recurrence-free survival (RFS) was slightly better in the SLNB group than in the END group (P=0.427). The 5-year overall survival (OS) rate was 89.9% in the SLNB group versus 91.9% in the END group (P=0.737). In a propensity-matched subgroup analysis, the type of neck management did not affect RFS or OS.Conclusion. SLNB showed non-inferior oncologic outcomes compared to END in patients with cN0 tongue squamous cell carcinoma.